Trueness and precision analysis of crown margins on digital casts produced by various dental scanning systems - Wei-Ling Wu; Chin-Wei Wang; Hui-Yin Nam; Wei-Chun Lin (Journal of Dental Sciences, 2025)
Background/Purpose: Digital dental scanning systems play a crucial role in producing precise dental restorations. This study aimed to evaluate the impact of different dental scanning devices on the trueness and precision of crown margins designed from digital models. It also focused on the influence of scanners and design software system alignment. Materials and methods: A standard dental cast was scanned using two intraoral scanners (Trios 3, Primescan) and three desktop scanners (S3, E3, X5). Crown designs were created for each cast using dental design software (inLab SW 16.1, Dentsply Sirona), resulting in a total of 25 digital crown files. These files retained only a 1 mm height from the cervical margin toward the occlusal direction for margin analysis. Root mean square error (RMSE) values were calculated to assess trueness and precision. Results: The trueness values for the same scanner ranged from 23.4 ± 4.1 μm to 42.1 ± 11.8 μm. Primescan (23.4 ± 4.1 μm) and X5 (29.7 ± 7.0 μm), which belonged to the same system as the design software, demonstrated superior accuracy (P > 0.05). No significant difference in trueness was observed between the intraoral scanner (Primescan) and the desktop scanner (X5) within the same system (P > 0.05). However, significant differences in trueness and precision were identified between systems (P < 0.05). Conclusion: The type of scanner and its system alignment significantly influenced the accuracy of crown margins. Ensuring compatibility between scanning devices and design software in clinical practice could enhance the precision of dental restorations.